ANALYZE THE IMPACT OF SATISFACTION, QUALITY, AND EXPERIENTIAL MARKETING ON TWITTER’S WORD OF MOUTH IN ECONOMICS AND BUSINESS FACULTY STUDENTS OF BRAWIJAYA UNIVERSITY - M. Khoirul Anam A (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Satisfaction, quality, and experiential marketing are influencing parts that create a product’s or service’s word of mouth communication. Word of mouth is the most effective promotion strategy in order to promote a product or service. Social networks nowadays are a requirement to socialize, one of them is Twitter. Twitter success could be affected by a good word of mouth in it’s marketing. Satisfaction, quality, and experiential marketing are important things in creating a word of mouth so the consumer encourage their friends and colleagues to use Twitter as a social networks too. A good word of mouth created only if consumer feels that the product or service brings a good satisfaction, quality, and experiential marketing. This study aims to explain the impacts of satisfaction, quality, and experiential marketing on Twitter’s word of mouth in Economics and Business Faculty students of Brawijaya University. This research use explanatory research approach that aims to explain causality among variables using hypothesis testing. Data is collected by survey using questionnaires for Economics and Business students of Brawijaya University. Purposive sampling is used as sampling method and gained 80 respondents. To test the hypothesis, multiple regression analysis is done. The results of multiple regression analysis shows that the following variables: satisfaction, quality, and experiential marketing have significant influence on word of mouth. Keyword: satisfaction, quality, experiential marketing, word of mouth.